0
$\begingroup$

So I've been given one question from my colleague, which needs to prove using below premises in order to draw a certain conclusion (see hypothesis below).

I've been doing this from last night and by out of luck, I can't get the hypothesis right, even by referring to Wikipedia rules table here.

Premise 1: $(\neg P \rightarrow Q) \rightarrow R$

Premise 2: $P \rightarrow R$

Premise 3: $Q \rightarrow R$

Hypothesis: $Q \rightarrow (P \rightarrow R)$

From my observation, by using the first premise, I can draw out the second and third premises, but then I getting stuck there.

1) $(\neg P \rightarrow Q) \rightarrow R$

2) $\neg(\neg P \rightarrow Q) \vee R$

3) $\neg (\neg \neg P \vee Q) \vee R$

4) $\neg (P \vee Q) \vee R$

5) $(\neg P \wedge \neg Q) \vee R$

6) $(\neg P \vee R ) \wedge (\neg Q \vee R)$

7) $(P \rightarrow R ) \wedge (Q \rightarrow R)$

Can somebody point out what steps should I do in order to draw the hypothesis conclusion from above three premises?

$\endgroup$
1
$\begingroup$

From Premise 2: Suppose $(P\rightarrow R)$. Then whenever $Q$ is true, $(P\rightarrow R)$ is true (by our premise). So $Q\rightarrow (P\rightarrow R)$.

From Premise 3: Suppose $(Q\rightarrow R)$. Then whenever $Q$ is true and $P$ is true, $R$ is true (by our premise). So whenever $Q$ is true, $P\rightarrow R$ is true. So $Q\rightarrow (P\rightarrow R)$.

If you're not happy with this informal style of reasoning, here's another straightforward option: note that $Q\rightarrow (P\rightarrow R)$ is equivalent to $\lnot Q\lor (P\rightarrow R)$, which is equivalent to $\lnot Q\lor \lnot P\lor R$, so it follows immediately from $\lnot P\lor R$ (Premise 2) and from $\lnot Q\lor R$ (Premise 3) by the rule called Addition on Wikipedia's list (you're always free to add another term to a disjunction).

| cite | improve this answer | |
$\endgroup$
1
$\begingroup$

I note that the Hypothesis can be inferred from each of the Premises alone ... Maybe that was the whole exercise?

OK, so here are 3 proofs, each starting with a different premise.

Proof from Premise 1:

  1. $(\neg P \rightarrow Q) \rightarrow R$ Premise 1

  2. $\quad Q$ Assumption

  3. $\quad \quad P$ Assumption

  4. $\quad \quad \quad \neg P$ Assumption

  5. $\quad \quad \quad Q$ Reiteration 2

  6. $\quad \quad \neg P \rightarrow Q$ $\rightarrow$ Intro 4-5

  7. $\quad \quad R$ $\rightarrow$ Elim 1,6

  8. $\quad P \rightarrow R$ $\rightarrow$ Intro 3-7

  9. $Q \rightarrow (P \rightarrow R)$ $\rightarrow$ Intro 2-8

Proof from Premise 2:

  1. $P \rightarrow R$ Premise 2

  2. $\quad Q$ Assumption

  3. $\quad P \rightarrow R$ Reiteration 1

  4. $Q \rightarrow (P \rightarrow R)$ $\rightarrow$ Intro 2-3

Proof from Premise 3:

  1. $Q \rightarrow R$ Premise 3

  2. $\quad Q$ Assumption

  3. $\quad \quad P$ Assumption

  4. $\quad \quad R$ $\rightarrow $ Elim 1,2

  5. $\quad P \rightarrow R$ $\rightarrow$ Intro 3-4

  6. $Q \rightarrow (P \rightarrow R)$ $\rightarrow$ Intro 2-5

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Can I know what is "Intro" and "Assumption"? I never heard or learn about these before in my logic class. $\endgroup$ – Mohd Shahril Apr 12 '17 at 5:24
  • $\begingroup$ @MohdShahril They are explained in the Wikipedia page you listed in your post. $\endgroup$ – Bram28 Apr 12 '17 at 12:22

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.